An eye‐movement analysis of the refutation effect in reading science text. (24th May 2016) - Ariasi, N.; Hyönä, J.; Kaakinen, J.K.; Mason, L.
Abstract: In this study, we used eye‐tracking methodology for deeper understanding of the refutation text effect on online text comprehension. A refutation text acknowledges the reader's alternative conceptions about a phenomenon, refutes them and presents the correct conceptions. We tested two hypotheses about its facilitation effect: the coherence hypothesis (refutation text is more coherent than standard text, thus facilitating comprehension) and the elaboration hypothesis (refutation text involves deeper processing, thus facilitating comprehension). Forty university students read one refutation text and one non‐refutation text about two science topics. Offline data confirmed that refutation text readers recall more scientific facts than non‐refutation text readers. Online eye‐tracking measures revealed both an increase and a decrease in reading time in response to the refutation statements. Topic‐medial text sentences with the correct science facts were fixated for a shorter time when first encountered in the refutation text. Refutation statements, however, increased integrative processing at the end of each text paragraph, as indexed by longer look‐back fixation times on topic‐final sentences with the science concepts, as well as longer look‐back fixation times directed to the refutation statements. These findings support the elaboration hypothesis and are discussed in the light of current accounts of the refutation effect for theory development and educational practice. Lay Description: What is already known about this topic: Science texts are often challenging to read, especially when the reader has misconceptions about the topicand must undergo conceptual‐change learning in order to successfully comprehend the text. A specific type of text, the refutation text, mayact as a powerful resource in facilitating conceptual change, but findings from process‐oriented investigations have been inconclusive with respect to its efficacy in this regard. What this paper adds: Refutation statements lead to faster processing of scientific facts that contradict commonly held misconceptions during the first‐pass reading. Refutation statements also encourage readers' later integrative processing during rereading, to monitor and ensure resolution of the conflict between their own conceptions and the conceptual information contained within the text. Implications for practice and/or policy: Immediate introduction of new science concepts in an expository text may not benefit readers' comprehension when they have existing misconceptions within the relevant knowledge domain. The use of sentences explicitly refuting readers' misconceptions has the potential to induce and sustain the conscious and deliberate processing that is required for them to become aware of the conceptual conflict, increasing their likelihood of resolving it. Update made on 05 November 2016, after first online publication: Since the publication of this article, a Practitioner Notes section has been implemented for this journal. This article has been updated with the Practitioner Notes section.